2021
DOI: 10.18400/tekderg.606620
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Analysis of Symmetrically Laminated Rectangular Thin Plates under Biaxial Compression

Abstract: In this parametric study, the buckling analysis of symmetrically laminated rectangular thin plates subjected to biaxial compression is presented. The simply supported boundary condition is considered at the edges of the symmetrically laminated quasi-isotropic, crossply and angle-ply plates. The Rayleigh-Ritz Method is used to specify the critical buckling load of the plates based on the Classical Laminated Plate Theory (CLPT). A convergence study is achieved by increasing the number of parameters of assumed sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Similar to the results found in the previous studies of the authors [30] in which they analyzed rectangular plates, although the critical buckling loads of some plates in superelliptical plates are the same in this study, these results change when the aspect ratio changes. For instance, LT8 and LT19 plates have equal critical buckling loads in a/b=1 case, but mode shapes are different (Figure B1).…”
Section: Effect Of Lamination Types Boundary Conditions and Aspect Ratiossupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to the results found in the previous studies of the authors [30] in which they analyzed rectangular plates, although the critical buckling loads of some plates in superelliptical plates are the same in this study, these results change when the aspect ratio changes. For instance, LT8 and LT19 plates have equal critical buckling loads in a/b=1 case, but mode shapes are different (Figure B1).…”
Section: Effect Of Lamination Types Boundary Conditions and Aspect Ratiossupporting
confidence: 91%
“…It was observed that from the results of highest value for the lowest critical buckling loads (N cr ) of super-elliptical plates (n=10), angle-ply plates are more advantageous than crossply and quasi-isotropic plates for lowest aspect ratio is (a/b=1, 1.2 and 1.4). Besides, quasiisotropic plates are more advantageous than others for highest aspect ratios (a/b=1.6, 1.8 and 2) similar the rectangular plate in previous work [30] for the simply supported boundary condition. However, quasi-isotropic plates are more advantageous than others for all aspect ratios for clamped boundary conditions.…”
Section: Effect Of Lamination Types Boundary Conditions and Aspect Ratiosmentioning
confidence: 51%
See 2 more Smart Citations